2020
DOI: 10.1007/s40200-020-00555-8
|View full text |Cite
|
Sign up to set email alerts
|

Substituting white rice with brown and black rice as an alternative to prevent diabetes mellitus type 2: a case-study among young adults in Yogyakarta, Indonesia

Abstract: Purpose The purpose of this study is to explore the preference and acceptance of white rice substitution with brown and black rice among young adults in Indonesia to prevent diabetes. Methods This study used a qualitative design. Rice preference deeply explored using focus group discussion as a case-study. 85 informants with an average of ages 20 years old were divided into several groups. Several topics to discuss include the reasons to accept or reject brown and black rice, knowledge, attitude, motivation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…Red rice is gaining popularity in Japan as a functional food because of its high polyphenols and anthocyanin content (Itani & Ogawa, 2004;Ling et al, 2001). White rice is known to have a higher glycemic index than other types of staple foods such as brown rice, whole grain, and barley (Helmyati et al, 2020). Black rice is one of the new rice that has a lower patronization rate (Helmyati et al, 2020).…”
Section: Rice Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…Red rice is gaining popularity in Japan as a functional food because of its high polyphenols and anthocyanin content (Itani & Ogawa, 2004;Ling et al, 2001). White rice is known to have a higher glycemic index than other types of staple foods such as brown rice, whole grain, and barley (Helmyati et al, 2020). Black rice is one of the new rice that has a lower patronization rate (Helmyati et al, 2020).…”
Section: Rice Typesmentioning
confidence: 99%
“…White rice is known to have a higher glycemic index than other types of staple foods such as brown rice, whole grain, and barley (Helmyati et al, 2020). Black rice is one of the new rice that has a lower patronization rate (Helmyati et al, 2020). Together with brown rice, black rice is higher in fiber and antioxidants than white rice (Hernawan & Meylani, 2016).…”
Section: Rice Typesmentioning
confidence: 99%
“…As discussed earlier, compared with white rice, WGR has lower digestibility both in vivo in humans and in vitro, due to its higher levels of dietary fiber, GABA, ORZ, polyphenols, vitamins, and minerals (Balakrishnan et al., 2019; Klunklin & Savage, 2018; Thiranusornkij et al., 2019; P. Wu et al., 2017). Large cohort studies indicated that replacing white rice with 50 g of brown rice per day reduced the risk of type 2 diabetes by 16% (de Munter et al., 2007; Sun et al., 2010), and results from controlled trials in the short term (up to 3 months) also showed that brown rice consumption could control the blood glucose level and prevent diabetes (Helmyati et al., 2020; Ito et al., 2005; Karupaiah et al., 2011; Mohan et al, 2014; Wedick et al., 2015). The results and mechanisms of glucose metabolism as regulated by WGR and reported in the literature are summarized in Table 3 .…”
Section: Regulation Of Glucose Metabolism By Wgrmentioning
confidence: 99%
“…Another study found that substituting white for brown and black rice is still challenging for young adults in Indonesia. Several barriers make further efforts needed to increase brown and black rice consumption (Helmyati et al, 2020). More significant efforts are needed to apply this ingredient branding strategy, mainly in groups that have not regularly consumed pigmented rice.…”
Section: Figure 4 Cbbe Pyramid Diagnosis For Occasional Consumers Of ...mentioning
confidence: 99%